Perception and Behavior in Skincare Routine During the Covid-19 Pandemic - Inneke Jane Hidajat; Maureen Miracle Stella; Jessica Alysia; Maureen Widjaja; Rika Zaskia; Regina Regina (Indonesian Journal of Global Health Research, 2025)
In the COVID-19 pandemic, several policies have been implemented such as the use of masks and social distancing. This has an impact on lifestyle changes such as skincare routines. The aim of this study was to obtain a demographic, behavioral, and perception overview of skincare use before and during the pandemic in medical students. This cross-sectional study was conducted by distributing a Google form questionnaire to FKIK Unika Atma Jaya students from the 2016-2021 intake. The inclusion criteria used were as follows: (1) FKIK Atma Jaya students from the 2016-2021 intake; (2) Students who completed the questionnaire until the end. Medical students demonstrated a high level of skincare knowledge but showed uncertainty regarding product composition and safety aspects. Their behavior indicated a strong focus on appearance and trust in brand quality, though opinions were divided on halal certification. Despite a strong demand for skincare products, makeup usage declined. Most respondents were aware of skincare benefits and potential side effects, but uncertainty arose about ingredients and disinfecting. This study explored the perceptions and behaviors of medical students regarding skincare use before and during the COVID-19 pandemic. Health promotion is urgently needed to prevent skin disorders due to skincare.